Fat necrosis mimicking liposarcoma in a patient with pelvic lipomatosis. CT findings - BALTACIOĞLU, FEYYAZ (My University, 2003)
Pelvic lipomatosis is a rare condition characterized by an overgrowth of normal fat in the perirectal and perivesical spaces. The most important differential diagnosis is liposarcoma. We present a case of pelvic lipomatosis associated with a mass, which was diagnosed radiologically as a liposarcoma, but surgical biopsy result revealed fat necrosis.
Keywords: Humans; Aged; Tomography, X-Ray Computed; Male; Follow-Up Studies; Contrast Media; Diagnosis, Differential; Biopsy, Needle; Colonic Neoplasms; Fat Necrosis; Lipomatosis; Liposarcoma; Pelvis; Radiographic Image Enhancement